Control over Financial Sustainability of the Enterprise in the Real Sector of Economic Activity - I. V. Korneeva; G. N. Rusakova (Управленческие науки)
Improving the quality of the company’s management implies the improvement of procedural and methodical support in the company’s financial performance evaluation as well as in planning its activities. To ensure high organizational effectiveness the company’s management needs to implement a strategy aimed at strengthening its financial sustainability and solvency. Along with this important area of the company’s strategic management there is its current activities analysis and further development plans design. Modern manufacturing organization requires a qualitative assessment of financial performance. First and foremost, the financial condition of an enterprise is evaluated by its financial sustainability and solvency. The analysis of an entity’s financial soundness is a critical step in the evaluation of its activities and financial and economic well-being. It reflects the effect of the current development, as well as investment and financial development. Insufficient financial stability leads to insolvency and even bankruptcy of the organization. Therefore, financial sustainability is the key to survival and the basis of the stability of a particular company in the future. The degree of a companiy’s financial stability primarily interestes investors and creditors, as they make their investment decisions in the company based on the evaluation of its financial sustainability. Therefore, the control over the company’s financial stability is of high importance today. The article analyzes modern approaches and current practices in the evaluation of enterprise’s solvency and financial stability in the real sector of economic activity - i.e. of the Moscow leather factory CJSC “Medvedkovo”.